A software-defined reconfigurable baseband digital communication system implemented in C54x - Ng, William, Jr. R.; Ojeda, Ma Cristina C.; Uy, Amiel Anthony C. (2005)
The project made use of the concept of software-defined radios and takes advantage of its reconfigurability to provide the academe an affective learning tool for students taking up Digital Communications. The software-defined baseband digital communication system implemented in TITMS320VC5402 is a project that demonstrates the reconfigurably using software in a simple digital communication system. Being software-defined in nature, this project maximizes the advantage of a reconfigurable system. The system, consisting of the transmitter and the receiver was implemented on separate boards and the Telecommunications Instructional Modeling System (TIMS) served as the channel. The selection of blocks implemented and their parameters may be controlled by the user via a Graphical User Interface (GUI), which was developed through the use of the Texas Instruments Code Composer Studio (CCS) Link to Matlab. A text file was used as input and the contents of the file are recovered at the receiver. The Bit Error Rate (BER) was computed for different configurations to assess the system's performance.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Digital communications; Wireless communication systems; Baseband digital communication system; Telecommunications Instructional Modeling System (TIMS).; Code Composer Studio (CCS).